Copper is required for oncogenic BRAF signaling and tumorigenesis - Brady, Donita C. (2014)
The BRAF kinase is mutated, typically V600E, to induce an active oncogenic state in a large fraction of melanoma, thyroid, hairy cell leukemia, and to a lesser extent, a wide spectrum of other cancers(1,2). BRAF(V600E) phosphorylates and activates the kinases MEK1 and MEK2, which in turn phosphorylate and activate the kinases ERK1 and ERK2, stimulating the MAPK pathway to promote cancer(3). Targeting MEK1/2 is proving to be an important therapeutic strategy, as a MEK1/2 inhibitor provides a survival advantage in metastatic melanoma(4), which is increased when co-administered with a BRAF(V600E) inhibitor(5). In this regard, we previously found that copper (Cu) influx enhances MEK1 phosphorylation of ERK1/2 through a Cu-MEK1 interaction(6). We now show that genetic loss of the high affinity Cu transporter Ctr1 or mutations in MEK1 that disrupt Cu binding reduced BRAF(V600E)-driven signaling and tumorigenesis. Conversely, a MEK1-MEK5 chimera that phosphorylates ERK1/2 independent of Cu or an active ERK2 restored tumor growth to cells lacking Ctr1. Importantly, Cu chelators used in the treatment of Wilson disease(7) reduced tumor growth of both BRAF(V600E)-transformed cells and cells resistant to BRAF inhibition. Taken together, these results suggest that Cu-chelation therapy could be repurposed to treat BRAF(V600E) mutation-positive cancers.